The Architecture Identity of Jami Adji Amir Hasanoeddin Mosque in Kutai Kartanegara - Ema Dwi Arsita; Ema Yunita Titisari; Damayanti Asikin (International Journal Labs, 2023)
Jami Adji Amir Hasanoeddin mosque is a symbol of the cultural and historical development of the city, especially regarding the entry of Islam into Kutai Kartanegara. The arrival of Islam in the Kutai kingdom certainly brought great cultural influence and acculturation, including the mosque style. In the context of the development of an increasingly globalized city and as a symbol that supports the image of the city, the architectural identity of the Jami Adji Amir Hasanoeddin Mosque needs to be identified as a guide in facing possible changes. This study used a qualitative method with a descriptive approach. The data were collected through interviews and field observations. The units of observation are determined based on the research framework compiled from the theory of architectural identity. The unit of observation for architectural identity includes spatial organization, time, semantics, design principles, building form, building materials, and context with the environment. From the results of the study, it was found that there was acculturation of Kutai, Javanese, Malay, Middle Eastern, and Dutch Indis architecture from each unit of observation of Architectural Identity.